Pemanfaatan Musuh Alami untuk Pengendalian Hayati Hama Tanaman Pangan dan Sayuran Guna Mendukung Keberhasilan Pertanian Organik - Siti Herlinda (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Herlinda S. 2020. Use of natural enemies for biological control for insect pests of food crops and vegetables to support organic farming. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In organic farming, synthetic fertilizers and pesticides are not used in crop cultivation so that the agricultural products are healthy and high quality. For this reason, the use of natural enemies should be applied to support the successful application of organic farming. This paper aimed to review and discuss the role of natural enemies in biological control for pests of food crops and vegetables. This study was conducted with a literature study approach. From the results of the review that natural enemies have been successfully utilized for biological control for insect pests of the food and vegetable crops, namely from the predators, parasitoids and entomopathogens. Predators, for example Pardosa pseudoannulata, have been used with a conservation approach to control rice insect pests (Nilaparvata lugens). Parasitoids, such as egg parasitoids (Trichogramma spp.) have been released to control Helicoverpa armigera eggs that attacked maize and soybeans. Entomopathogenic fungi that have been shown to kill insect pests of vegetables (Spodoptera litura) and maize (Spodoptera frugiperda) are Penicillium citrinum, Talaromyces diversus, Beauveria bassiana, and Metarhizium anisopliae. So, natural enemies are very useful in controlling pests of food crops and vegetables. The presence and persistence of natural enemies in the field can support the success in application of organic farming.